Giving the Benefit of the Doubt. Issue 2 (15th March 2018) - Faulkner, Paul
Abstract: Faced with evidence that what a person said is false, we can nevertheless trust them and so believe what they say – choosing to give them the benefit of the doubt. This is particularly notable when the person is a friend, or someone we are close to. Towards such persons, we demonstrate a remarkable epistemic partiality. We can trust, and so believe, our friends even when the balance of the evidence suggests that what they tell us is false. And insofar as belief is possible, it is also possible to acquire testimonial knowledge on those occasions when the friends know what they tell us. This paper seeks to explain these psychological and epistemological possibilities.